Is osteophyte located in the inferior of the intermeniscal ligament an indication for the surgical treatment of degenerative meniscal tear? - Özbek, Emre Anıl; Gezer, Mehmet Can; Karaca, Mustafa Onur; Kavak, Mustafa; Akmeşe, Ramazan (The European Research Journal, 2023)
Objectives: Our study aimed to determine how often the osteophyte located underneath the anterior intermeniscal ligament is observed in patients who underwent arthroscopic surgery due to degenerative meniscal tears, how often this osteophyte can be diagnosed by magnetic resonance imaging, and whether this osteophyte could be an indication for the surgery to be performed for degenerative meniscopathy. Methods: Our retrospective study included 47 patients operated for degenerative meniscus tears between 2017 and 2018, with a minimum follow-up of 2 years. Visual analog scale (VAS), Lysholm knee, and Western Ontario Meniscal Evaluation Tool (WOMET) scores were applied to all patients included in the study preoperatively and at the postoperative 3rd, 6th, 12th, and 24th months. The operated patients were grouped into two groups with and without osteophytes beneath the anterior intermeniscal ligament in magnetic resonance imaging (Group A and B). Preoperative and postoperative values of the patients were compared among themselves. Results: The average age of the patients included in our study was 57 (range: 42 to 72) years. Forty (85%) participants were female. Osteophyte was detected in 36.1% (n = 17) of the patients in preoperative magnetic resonance imagings (Group-A). There was a statistically significant difference between preoperative VAS, Lysholm, and WOMET scores and postoperative 3rd, 6th, 12th, and 24th months (p < 0.05). Mean follow-up time was 32 (range: 24 to 60) months. Conclusions: We believe that arthroscopic control of the inferior intermeniscal ligament for the presence of any osteophytes in patients treated surgically for degenerative meniscal tears is one of the main steps of this surgery.